Drawing on Siedentop's Legacy to Revisit Systematic Observation of Teaching: Identifying and Addressing Key Validity and Reliability Questions. Issue 1 (2nd January 2023) - Tsangaridou, Niki; Charalambous, Charalambos Y.
ABSTRACT: Focusing on systematic observation, one of the most potent methods of studying teaching quality, represents one of the numerous contributions of Daryl Siedentop to the profession. While he had a clear focus on issues of validity and reliability concerning systematic observation, over the past decades, attention to such issues appears to have eroded. By drawing on Siedentop's contribution to systematic observation and the guidance he provided on gathering quality data, in this paper we discuss the lessons learned from his work regarding what needs to be observed, how, by whom, and under what conditions – all addressing important validity and reliability issues. We argue that closely attending to these issues is critical not only for reinvigorating a research field initiated by scholars such as Siedentop but also for restoring its key role in studying teaching quality.